EFFECT OF DIFFERENT CONCENTRATIONS OF BOVINE SERUM ALBUMIN ON IN VITRO MATURATION OF BUFFALO OOCYTES - MISTRY, C N; DHAMI, A J; SUTHAR, V S; RANK, D N; JOSHl, C G (The Indian Journal of Animal Reproduction, 2010)
A total of 456 fresh ovaries of Surti buffaloes without CL were obtained from the local abattoir. By:;!icing metl 10d of 1409 oocytes were recovered with an average of 3 .09 oocytes per ovary. The averagerecovery rate of grade A, Band C oocyte were 1.02, 1.22 and 0.85, respectively. The overall maturationrate with 0.05, 0.1, 0.3, 0.6 and 0.9 per cent concentration of BSA (Sigma) in TCM"199 mediumsupplemented with 10 IU/ml of eCG and 5 IU/ml of hCG was found to be 44.52, 50.99, 59.02, 84.43 and64.29 per cent (P
Keywords: Buffalo oocytes; Bovine serum albumin; In vitro maturation